Optimizing Lecturers’ English Proficiency through TOEFL Mentoring via e-Learning and Zoom Meeting - Durratul Hikmah; Dewi Halimatus Sya’diyah (Universitas Nurul Jadid, 2024)
One of the main challenges that lecturers face in preparing for doctoral studies is meeting the requirements for English proficiency certificates, such as TOEFL, which often require high scores. This challenge is mainly felt by lecturers who are not graduates of the English study program. To help address this issue, the Community Service (PkM) program aims to enhance the English proficiency of lecturers at Universitas Nurul Jadid through e-learning-based TOEFL mentoring based on e-learning and Zoom Meeting. The method of implementing this program includes the stage of planning, implementation, as well as monitoring and evaluation, with a total of 33 lecturers from Universitas Nurul Jadid. This program involves the use of online learning technology to facilitate learning flexibility, considering the lecturers’ busy schedules with teaching and administrative responsibilities. The results of the program showed a significant improvement in participants' TOEFL scores from pre-test to post-test. Formative and summative evaluation data, including mid-test and post-test, indicate that this technology-based approach effectively enhances lecturers’ English proficiency. The program not only managed to achieve its main goal but also provided insights for the development of similar programs in the future.